Algorithm for calculating the profile of the feeder cutting band rotary snow blower - Aleshkov D.S.; Korchagin P.A.; Letopolsky A.B.; Teterina I.A. (Научно-технический вестник Брянского государственного университета)
The article reflects the calculation schemes for the movement of a snow particle along the surface of the cutting strip and the calculation scheme for determining the angle of inclination of the cutting strip of the feeder of a rotary snow blower. The relationships that determine the direction of action of the centrifugal force projections and the conditions that determine the nature of the equations of motion of a snow particle along the cutting strip and the possible phase states of the mechanical system “cutter of the vertical feeder of a rotary snow blower – transported snow particle” are presented. Using the example of a low-power rotary snow blower with a vertical feeder, the boundary of the change in the direction of action of the projections of the centrifugal force of inertia is graphically shown. The nature of the change in the equations of motion of the mechanical system under consideration is described. A diagram of the construction of the profile of the cutting strip of the vertical feeder cutter of a rotary snow blower is presented. An algorithm has been proposed for constructing the profile of the cutting strip of a vertical feeder cutter, which ensures the required time for the snow particle to remain in the space of the cutter. The use of an algorithm when designing the working parts of rotary snow blowers can slow down the process of formation of a snow prism in the area of the loading window of the propelling apparatus of a rotary snow blower.